Language Acquisition Through Cartoons: A Case Study of a 3-Year-Old Child - Karsana, I Wayan (Lingual Journal of Language and Culture; Vol 17 No 1 (2024): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2024.v17.i01.p04, 2024)
Children are the most precious possessions owned by the family. Every child's growth and development is different. Growth is a change in body size and shape while development is a gradual mental change in a certain period. Child development can be seen from how language acquisition in this study more focused on children aged 3 years 8 months. The acquisition of a second language (L2) in the form of Indonesian is mostly obtained from watching cartoons. Age 0-4 years is a period when the development of children's intelligence begins to form. The acquisition of L2 in this study was studied based on Psycholinguistics where in addition to the language spoken there was also the development of behavior and attitude of the child hermself obtained from watching cartoons. The selection of entertainment programs is an important concern for parents in build the character of children. Key words: Children's language acquisition, Indonesian, second language, psycholinguistics